Mediasi Profesionalisme Tehadap Kinerja Pegawai: Pengaruh Emotional Intelligence, Intellectual Intelligence dan Work Experience - Suciningtyas, Santi; Wuriah Ningsih, Diah (CV. Publikasi Indonesia, 2022)
The success of the organization is influenced by a process that significantly affects the success of the organization with the roles of managers and workers synergizing with each other to set expectations, evaluate results and reward performance. The purpose of this study was to determine the effect of mediation of professionalism on the effect of emotional intelligence, intellectual intelligence and work experience on employee performance. The data analysis method used is indirect impact analysis and sub-analysis. Section 90 of this research analysis involves government employees at the Pamelang Education and Culture Office. The results of this study have a significant influence between the Emotional Intelligent variable (X1) on the Employee Performance variable (Y), there is a significant influence between the Intellectual Intelligence variable (X2) on the Employee Performance variable (Y), there is a significant influence between the Work Experience variable (X3) on the Employee Performance variable (Y), there is a significant effect between the Emotional Intelligent variable (X1) on the Professionalism variable (Z) as a mediating variable and there is a significant influence between the Intellectual Intelligence variable (X2) on the Professionalism variable (Z) as a mediating variable, there is an influence There is a significant difference between the Work Experience variable (X3) and the Professionalism variable (Z) as a mediating variable in the Pemalang Education and Culture Office, and there is a significant effect between the Professionalism variable (Z) on the Employee Performance variable (Y) at the Pemalang Education and Culture Office. So it can be concluded that knowledge of emotional information and work experience has a direct effect on employee performance. Intellectual emotional intelligence and work experience have an indirect effect on professionalism. Mediation on employee performance. In addition, professionalism has a significant influence on employee performance.